2016
DOI: 10.1007/s13361-016-1429-6
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Structure and Degradation Analysis in Fingerprint Residues

Abstract: Abstract. GC-MS investigations were carried out to elucidate the aging behavior of unsaturated fatty acids in fingerprint residues and to identify their degradation products in aged samples. For this purpose, a new sample preparation technique for fingerprint residues was developed that allows producing N-methyl-N-trimethylsilyltrifluoroacetamide (MSTFA) derivatives of the analyzed unsaturated fatty acids and their degradation products. MSTFA derivatization catalyzed by iodotrimethylsilane enables the reliable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…In our experiment, the subjects with the highest BMI, that is, overweight individuals, and those with the lowest BMI, that is, underweight persons, had fingerprints with significantly wider ridges than subjects with normal BMI (Table ). In the case of people who are overweight, the results can be explained by the larger skin area as well as the greater amount of sweat and sebum produced and susceptibility to sweating . In the case of underweight people, the significantly wider friction ridge impression is probably due to the fact that this group was dominated by women, who as mentioned above had used emollients in the morning.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In our experiment, the subjects with the highest BMI, that is, overweight individuals, and those with the lowest BMI, that is, underweight persons, had fingerprints with significantly wider ridges than subjects with normal BMI (Table ). In the case of people who are overweight, the results can be explained by the larger skin area as well as the greater amount of sweat and sebum produced and susceptibility to sweating . In the case of underweight people, the significantly wider friction ridge impression is probably due to the fact that this group was dominated by women, who as mentioned above had used emollients in the morning.…”
Section: Resultsmentioning
confidence: 93%
“…The difference in the width of the ridges between the prints from women and men was 11% (p < 0.001). These results are surprising, as research by Pleik (6) shows that men secrete more sweat and sebum than women, which contributes to the durability of their prints (15). This is due in part to the number and distribution of sweat ducts, with men having more of them, as well as to hormone metabolism (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Pleik et al focused on the identication of degradation products of common fatty acids in ngerprints as potential tool for age determination. 5 Van Dam et al used uorescence spectroscopy to determine the relative amount of uorescent oxidation products to estimate the age of ngerprints from male donors up to three weeks old, within several days' accuracy. 6 Alternatively, Oonk et al, using a proteomics approach, suggested several potential protein markers to estimate ngerprint age.…”
Section: Introductionmentioning
confidence: 99%
“…fingerprint residues using GC/MS. They found that Δ6-Hexadecenoic acid and Δ8octadecenoic acid, as well as associated degradation products, could be useful in determining the age of a fingerprint left on a surface [23]. This information could ultimately be useful in a forensic investigation to exclude a fingerprint that was not deposited contemporaneous with the predicted time that the crime of interest occurred.…”
Section: Another Recent Study By Pleik Et Al Evaluated the Degradatimentioning
confidence: 99%